{Resolution of Hematocolpos in Adolescents Affected with Graft vs Host Disease} - Michala, L.; Vlachopapadopoulou, E.; Tsimaris, P.; Papaioannou, G.; Paisiou, A.; Peristeri, I; Michalacos, S.; Kitra, V. (Journal of Pediatric and Adolescent Gynecology, 2018)
© 2018 North American Society for Pediatric and Adolescent Gynecology Background: Bone marrow transplantation is a lifesaving procedure for a range of serious benign or malignant hematological conditions. A proportion of patients, however, will develop graft vs host disease (GVHD), acute or chronic, with serious long-term sequalae. Cases: We present 2 cases of hematocolpos that developed in adolescence because of vaginal synechiae due to GVHD. The condition was initially asymptomatic, resolved spontaneously at first and recurred. In 1 girl blunt lysis of the adhesions was performed with the patient under general anesthesia, followed thereafter by local hydrocortisone and estriol treatment. Summary and Conclusion: Genital symptoms might not be readily reported by adolescents after bone marrow transplantation. Physicians should be aware of possible late effects of GVHD on genitalia, inquire about symptoms, and be acquainted with addressing complications, such as vaginal obstruction.
Keywords: adolescence; Genital graft vs host disease; Graft vs Host Disease; Hematocolpos